PERAN GURU UNTUK MEMBINA SIKAP PESERTA DIDIK DALAM MENERAPKAN PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH ARRAHMATUL ABADIYAH KOTA BANJARMASIN - Ashabul Yamin; Syamsuni; Muhammad Rasyid Ridho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to outline how Aqidah Akhlak instructors at Madrasah Ibtidaiyah Arrahmatul Abadiyah, Banjarmasin Utara District, Banjarmasin City, influence students' attitudes toward Islamic education. The study employs a case study methodology and a qualitative approach. The Aqidah Akhlak teacher, the principal of the school, and students who served as informants were all involved in the data collection process, which included observation, interviews, and documentation. Data reduction, data display, and conclusion drawing are among the data analysis techniques employed, and source triangulation is used to guarantee data validity. The study's findings show that Aqidah Akhlak teachers have a significant impact on students' attitudes as educators, role models, facilitators, motivators, and assessors. The primary factor influencing students' moral development in daily life is the exemplary behavior of their teachers. Additionally, teachers use interactive techniques like discussion, storytelling, and habituation exercises to incorporate moral values into the learning process. However, a number of difficulties were discovered, such as the impact of the environment, the advancement of technology, and the short amount of time available for instruction. Teachers employ ongoing moral guidance, parent-teacher collaboration, and the use of technology to support learning activities in order to overcome these obstacles. In general, teachers play a critical role in developing students' moral character based on Islamic principles.